2016
DOI: 10.1177/1464884916673386
|View full text |Cite
|
Sign up to set email alerts
|

Journalism beyond democracy: A new look into journalistic roles in political and everyday life

Abstract: Journalism researchers have tended to study journalistic roles from within a Western framework oriented toward the media’s contribution to democracy and citizenship. In so doing, journalism scholarship often failed to account for the realities in non-democratic and non-Western contexts, as well as for forms of journalism beyond political news. Based on the framework of discursive institutionalism, we conceptualize journalistic roles as discursive constructions of journalism’s identity and place in society. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
282
1
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 277 publications
(318 citation statements)
references
References 52 publications
6
282
1
12
Order By: Relevance
“…The rationale for a strong focus on journalists' professional views has long been that what journalists reflect on about their work, is also a reflection of the work they actually do, even though this notion has been put in doubt in recent years (Tandoc, Hellmueller, and Vos 2013). While most research therefore now acknowledges that what journalists say they do is not always the same as what they actually do, there is still an understanding in the literature that through their discourse about professional roles, journalists constitute journalistic cultures that can be compared cross-nationally (Hanitzsch and Vos 2016).…”
Section: Comparing Journalistic Cultures Across Nations What We Can Lmentioning
confidence: 99%
“…The rationale for a strong focus on journalists' professional views has long been that what journalists reflect on about their work, is also a reflection of the work they actually do, even though this notion has been put in doubt in recent years (Tandoc, Hellmueller, and Vos 2013). While most research therefore now acknowledges that what journalists say they do is not always the same as what they actually do, there is still an understanding in the literature that through their discourse about professional roles, journalists constitute journalistic cultures that can be compared cross-nationally (Hanitzsch and Vos 2016).…”
Section: Comparing Journalistic Cultures Across Nations What We Can Lmentioning
confidence: 99%
“…Hanitzsch et al 2011;Weaver 1998;Weaver and Willnat 2012). However, conceptually and empirically such work has predominantly tended to focus on journalism's function in a democratic context, or at least its relationship with the political realm (Hanitzsch and Vos 2016). A strong focus has been on normative expectations of journalism's role in society, privileging certain kinds of journalism at the expense of others.…”
Section: Introductionmentioning
confidence: 99%
“…Hanusch 2012a; Hanusch and Hanitzsch 2013), these are few and far between and much research on journalistic roles continues to focus predominantly on traditional notions of journalism's relationship with political life. The result has been that roles addressing everyday life remain under-articulated (Hanitzsch and Vos 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As such, they are informed by "expectations, values, norms and standards defining how news people and organizations should and do work" (Hellmueller & Mellado, 2015, p. 4). As these tasks and duties are internalised during professional training and work, journalists develop corresponding personal and collective role conceptions, or beliefs about the expectations of others, which guide their actions on the job (Donsbach, 2008;Hanitzsch & Vos, 2018). Accordingly, journalistic role conceptions have been identified as one significant factor in explaining actual news production-alongside other factors, such as personal values, organisational culture, institutional routines and various systemic constraints (e.g., Preston, 2009;Shoemaker & Reese, 2014).…”
Section: Journalistic Roles and Role Conceptionsmentioning
confidence: 99%
“…This is problematic because several recent studies have indicated that the actual role performance of journalists often differs from their role conceptions, as stated in surveys, interviews and codes of conduct (Mellado et al, 2017;Tandoc et al, 2013). Moreover, research has long recognised that journalists regularly face conflicting expectations from their surrounding environment and must find ways to negotiate between and combine multiple roles in their work (Hanitzsch & Vos, 2018;Hellmueller & Mellado, 2015;Kramp & Weichert, 2014;Rosten, 1937;Tandoc & Takahashi, 2014).…”
Section: A Social-interactionist View On Journalists' Role Conceptionsmentioning
confidence: 99%